The perceptions of the mestizo teachers about the Miskito Students in URACCAN - García, Argentina (Bilwi :URACCAN, 2002)
This study looks at the effects of the multicultural context on the education system on the Atlantic Caribbean Coast of Nicaragua.
Incluye Índice
Col. Tesis
Keywords: 1. TRADITIONAL EDUCATION 2. MESTIZO TEACHERS